Endothelial dysfunction in arterial hypertension - cardiovascular complication risk factor - B. A. Namakanov (Кардиоваскулярная терапия и профилактика, 2005)
This review contains the results of the studies in pathophysiological basis of endothelial function (EF), and clinical methods for its assessment. Main neurohormonal mechanisms of EF regulation in healthy persons are compared. Diagnostic and prognostic value of EF disturbances, as cardiovascular event predictors, is analyzed in details. Modern data on pharmaceutical and non-pharmaceutical EF correction are presented. The authors also deliver a hypothesis on genetic causes for EF disturbances in humans.